2021
DOI: 10.1111/bld.12378
|View full text |Cite
|
Sign up to set email alerts
|

Lived experience and the social model of disability: conflicted and inter‐dependent ambitions for employment of people with a learning disability and their family carers

Abstract: Accessible Summary In the UK very few people with learning disability and/or autism and their family‐carers have a paid job although a lot of them may wish to work. National plans from the Government have not helped to change this. This article talks about a consultation we did on adults with learning disabilities and/or autism who attend day centres and their family‐carers. We asked about their current situation, their employment and the barriers to work. We found out that very few people with learning disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…With recent studies revealing that 44% -52% of those diagnosed with autism have learning difficulties, once they overcome the difficulty of simply adapting to their environments, understanding the information presented is an additional hurdle (Madge, 2021;Giri, Aylott, Giri, Ferguson-Wormley, & Evans, 2022;Mammarella, Cardillo, & Semrud-Clikeman, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With recent studies revealing that 44% -52% of those diagnosed with autism have learning difficulties, once they overcome the difficulty of simply adapting to their environments, understanding the information presented is an additional hurdle (Madge, 2021;Giri, Aylott, Giri, Ferguson-Wormley, & Evans, 2022;Mammarella, Cardillo, & Semrud-Clikeman, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most people with learning disabilities in paid employment also work under 16 h per week, most likely due to this being the maximum hours allowed before benefits are impacted (Hatton, 2018). Many people with learning disabilities do not want or are not able to have a job (Giri et al, 2021) and pressure to get a job and the threat of benefits sanctions can lead to anxiety and distress (Dearing, 2020; Watts et al, 2014). However, paid employment can be beneficial for many people with learning disabilities, and these individuals have a right to appropriate, well‐supported employment (Assembly UN General, 2006; Department of Health, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative rarity of formally employing people in these roles suggests that there are barriers to this. People with learning disabilities face numerous barriers to employment generally, such as the patchy provision of support, costs associated with transportation to work, low confidence, and negative social attitudes (Bates et al, 2017; Giri et al, 2021). Austerity in the past decade has led to an increase in short‐term jobs, putting people with disabilities at particular risk of losing benefits and not having them reinstated at the end of a short‐term contract (Bates et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that 44-52% of those diagnosed with ASD have additional learning disorders or difficulties. That being the case, once the population overcomes the physical barriers to entry, comprehending the educational material presented represents another obstacle [30][31][32]. Fortuitously, museums were prepared for the needs of diverse learners and already have a range of resources to assist.…”
mentioning
confidence: 99%